ANALISIS WACANA KRITIS FEODALISME DAN DISKRIMINASI PEREMPUAN JAWA DALAM NOVEL GADIS PANTAI KARYA PRAMOEDYA ANANTA TOER - Maria Endah Perwitasari; Retno Hendariningrum (Jurnal Ilmu Komunikasi, 2009)
As a literature in the form of novel, Gadis Pantai actually has a hidden meaning which Pramoedya wants to present as the author. The mistress practice is not only presented as a kind of discriminative behavior toward Javanese women, but also has a correlation with Pramoedya social background and ideology. This research methodology employed in this research is Sara Mills’ Critical Discourse Analysis model which focuses on feminism discourse. The nature of study using this model tends on political text writing related to author’s ideology and the extensive meaning that Gadis Pantai novel comprehensively expects to bring about. The results of this study show that Pramoedya Ananta Toer tends to explore injustice experienced by Javanese women represented by Gadis Pantai to criticize feudalism practices in Java. By presenting the injustice experienced by Gadis Pantai, Pramoedya Ananta Toer actually wants to awaken readers’ awareness and empathy towards what happened to Gadis Pantai. He also invites readers to fight injustice practices in all aspects, especially those which relate to Javanese culture which still employs social classes in its society, and places a woman as a secondary being after a man and as a suppressed one. Pramoedya employs a novel as media in transferring his thoughts and ideology to change social construction in Javanese society which has been inherited from generation to generation.